Faces of Soul: Music Genres and Dynamic Imaginaries - Pedro, Josep; Gutiérrez-Martínez, Begoña (CIC. Cuadernos de Información y Comunicación, 2020)
In this paper we study discourse genres based on their relationship with popular music. From a pragmatic perspective, we approach the historical evolution of soul in relation to the African-American civil rights movement. In order to examine the transformations of this music genre and its imaginary, we undertake a socio-semiotic analysis based on two paradigmatic examples: the song “Dancing in the Street” (Martha Reeves & The Vandellas, 1964) and the album What’s Going On (Marvin Gaye, 1971). These works embody and shape a dynamic imaginary that evolves in relation to the social and political experiences of the African-American community in the U.S. They represent and exemplify the two faces of soul: a happy and hopeful one; and a wounded and melancholic one.